Competitiveness of Indonesian Pepper in the International Market - Diamonds, Gabriella Pusparini Tasya Patricya; Harya, Gyska Indah; Fitriana, Nisa Hafi Idhoh (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Pepper productivity fluctuates and is also low at 0.46 tons/ha. The export volume and export value of Indonesian Pepper in the International Market are declining. In addition, there is intense competition among pepper exporting countries in the world. The objectives of this study are: to analyze the comparative advantage and competitive advantage of Indonesian Pepper in the International Market over a thirty-year time period from 1993 - 2022. As well as knowing the right policy implications based on pepper export problems in the International Market. The method used in the analysis of comparative advantage is Revealed Comparative Advantage (RCA) while in the analysis of competitive advantage using the Export Competitiveness Index (ECI). The type of pepper used in this study is dried or crushed or ground pepper seeds, with HS code 0904. The results of this study are that Indonesian Pepper is strongly competitive in terms of pepper exports in the International Market. Evidenced by the results of the RCA value of 9.55 or more than 1. So that Indonesia excels in terms of pepper exports in the International Market. Indonesia's RCA results are lower than India. However, it is higher than China. Whereas in the ECI results, Indonesia is competitively competitive. Evidenced by the results of the ECI value of 1.01 or more than 1. Policy implications in pepper exports are increased production, improved upstream and downstream processing, expansion of market share, and government support and policies. Improved production is expected to increase the volume of pepper exports.